In situ SEM study on tensile fractured behavior of Al/steel laser welding-brazing interface. (December 2022) - Xia, Hongbo; Li, Liqun; Tan, Caiwang; Yang, Jin; Li, Haoyue; Song, Wei; Zhang, Kaiping; Wang, Qian; Ma, Ninshu
Graphical abstract: Highlights: Dynamic fractured behaviors of Al/steel interface were observed by in–situ scan electron micrograph technology. Interface joined with 2 – 3 μm τ5 exhibited the optimum bonding strength of 205 MPa. Mechanisms for determination of bonding strength by metallurgical bonding, interplanar spacing mismatch and micro – defects were clarified. Abstract: Microcracks initiated and propagated behaviors in Al/steel interface determined interfacial bonding strength and this was observed by in situ scanning electron microscopy (SEM) technology. Interface without or with discontinuous intermetallic compound (IMC) had low bonding strength owing to insufficient metallurgical bonding. When interface was joined with 2–3 μm serration–shaped τ5 –Fe1.8 Al7.2 Si, largest bonding strength of 205 MPa was obtained. Microcracks initiated at protrusion of τ5 –Fe1.8 Al7.2 Si and then propagated to τ5 –Fe1.8 Al7.2 Si layer and τ5 –Fe1.8 Al7.2 Si/Al interface. When interface was joined with 3–5 μm θ–Fe(Al, Si)3  + τ5 –Fe1.8 Al7.2 Si, microcracks initiated at root of IMC layers and the interfacial bonding strength was 150 MPa. When interface was joined with 5–10 μm θ–Fe(Al, Si)3  + τ5 –Fe1.8 Al7.2 Si, microcracks initiated and propagated along IMC layer. Lower interfacial bonding strength (106 MPa) was produced owing to large lattice mismatch between θ–Fe(Al, Si)3 and τ5 –Fe1.8 Al7.2 Si, microdefects and higher residual stress. When interface was joined with 10 μm η–Fe2 (Al, Si)5  + θ–Fe(Al, Si)3  + τ5 –Fe1.8 Al7.2 Si, microcracks initiated and propagated along η–Fe2 (Al, Si)5 layer or steel/η–Fe2 (Al, Si)5 interface. Lowest bonding strength (64 MPa) was obtained resulted from pre–generated microcracks in η–Fe2 (Al, Si)5 layer, largest residual stress, crystal defects and abnormal aggregation of Si.